The evolution of terrorism in Russia in the years 2015-2022. Quantitative analysis of the phenomenon - Stempień, Marta (Przegląd Wschodnioeuropejski, 2023)
In the years 2015-2021, Russia’s rank in Global Terrorism Index became lower every year. In 2015 and 2016, it was classified as third among the European countries, behind Ukraine and France. In the following period (2017-2021), the United Kingdom also found itself ahead of Russia, which fell to the fourth position. The present article has the form of a quantitative analysis. The research goal is to identify trends related to terrorism that take place in the Russian Federation in the years 2015-2022 (in some parts, the analysis covers the time span between 2015 and 2021, due to lack of data). According to the hypothesis: The phenomenon of terrorism in Russia is closely related to the activities of jihadist organizations, and groups with a different profile pose a marginal threat. Quantitative analysis of the attacks conducted in the analyzed period will enable the verification of the hypothesis and determine the prospects for the development of this aspect.